2021
DOI: 10.1007/s00784-021-03971-z
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of acute pain and strain of the periodontium due to orthodontic separation on the occlusal tactile acuity of healthy individuals

Abstract: Objectives The aim of this study was to assess whether pain and strain of the periodontal ligament (PDL), induced by orthodontic separation, alter the somatosensory ability to perceive small thicknesses between occluding teeth (occlusal tactile acuity, OTA). Methods The OTA was tested at baseline (T0), using 9 aluminum foils (range 8–72 μm), randomly placed between the molar teeth, and 1 sham test (without foil), asking the participants whether they felt t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Bucci et al studied how pain and periodontal ligament stretching caused by tooth movement affect periodontal ligament tactile sensation [5]. Occlusal tactile acuity during occlusion was measured before insertion of the separator elastics, 24 hr after insertion of the elastics between the mesial and distal maxillary rst molars, and 7…”
Section: Comparison Of Vas and Intensitymentioning
confidence: 99%
See 2 more Smart Citations
“…Bucci et al studied how pain and periodontal ligament stretching caused by tooth movement affect periodontal ligament tactile sensation [5]. Occlusal tactile acuity during occlusion was measured before insertion of the separator elastics, 24 hr after insertion of the elastics between the mesial and distal maxillary rst molars, and 7…”
Section: Comparison Of Vas and Intensitymentioning
confidence: 99%
“…Occlusal tactile acuity was evaluated by having the teeth bite aluminum foil of various thicknesses. The results demonstrated that occlusal tactile acuity was reduced signi cantly compared to that before the use of separator elastics [5]. Stimulation of brain regions associated with the pain response is regarded as interfering with and delaying the transmission of tactile stimulation, possibly resulting in reduced tactile sensation.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…When the periodontal ligament responds to loads applied to the tooth, it produces tactile, pressure, and vibration sensations [ 1 3 ]. Periodontal ligament sensations are extremely sensitive, able to detect even micrometer thickness [ 4 , 5 ] and playing important roles in detecting food mass size and hardness [ 6 ] and in adjusting the jaw position and bite force [ 7 ]. The presence of the periodontal ligament is also necessary for moving teeth.…”
Section: Introductionmentioning
confidence: 99%
“…Occlusal tactile acuity was evaluated by having the teeth bite aluminum foil of various thicknesses. The results demonstrated that occlusal tactile acuity was significantly lower than that before the use of separator elastics [ 5 ]. Stimulation of brain regions associated with the pain response presumably interferes with and delays the transmission of tactile stimulation, possibly reducing tactile sensation.…”
Section: Introductionmentioning
confidence: 99%